Evaluación del cambio del factor de recobro utilizando modelos de gestión de calor de inyección de vapor en yacimientos de crudo pesado en un campo brasileño (2022)
Cyclic steam injection is an advanced recovery method that allows the reduction of crude oil viscosity, being widely used for heavy and extra-heavy oil reservoirs. The Energy management models, enunciated by five authors, are used to increase the production and the recovery factor in the applied field and the oil industry by continuous steam injection. To successfully carry out the implementation of the models in the field and have favorable results for the investigation, it is necessary to consider the thermal maturity of the reservoir, the steam injection times, the quality of the steam, the lifetime of the reservoir and a rigorously planned economic evaluation. In the present investigation, we analyze the performance and application of the continuous steam injection thermal method using as study material a Brazilian field that is in the formation of Amazonas, Brazil, identifying the high impact variables and simulating the process using CMG simulator.